Alternative Approach to Conventional River Water Treatment Using Natural Coagulant - Selvaraj, Komathy; Sidek, Lariyah Mohd; Mohd Noor, Megat Johari Megat; Tamunaidu, Pramila; Goto, Masafumi (International Journal of Engineering and Technology, 2018)
Extensive studies have been conducted to discover natural, efficient and cost-saving coagulants for water treatment. Meanwhile, chemical coagulants are being used conventionally in drinking water treatment. This study investigates the efficacy of diatomite as a natural coagulant in river water treatment. First, synthetic turbid water was used to validate the coagulant efficiency. Then, coagulation and flocculation behaviors were studied by using the river water samples from Langat River and Semenyih River. Turbidity removal efficiency of synthetic turbid water revealed that a low dosage of 3.5 mg/L could reach turbidity reduction of 83.46%. The turbidity reduction for Semenyih River water with initial turbidity of 31.8 NTU was achieved at 91.7% with 18 mg/L dosage at pH of 7.4 whereby, for Langat River water with an initial turbidity of 43.3 NTU, the turbidity reduction was achieved at 94.5% with a dosage of 26 mg/L at pH of 8.0. These results showed that water turbidity removal was influenced by both high and low natural organic material. This is because the best dosage of coagulant is indirectly proportional to the molar mass of natural organic material. In conclusion, diatomite is a promising material to be used as a natural coagulant in water treatment applications. Â